PENINGKATAN HASIL BELAJAR KIMIA SISWA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) DI SMAN 92 JAKARTA - Yohana Junita; Leony Sanga Lamsari Purba (Jurnal Dinamika Pendidikan, 2019)
ABSTRACT This research is a pure experimental study with a pre-test and post-test onlycontrol design. The population includes all students of class XI MIPA SMAN 92Jakarta Semester I Academic Year 2018/2019. The study sample consisted oftwo classes with a sample size of 58 students determined by purposive sampling.The research instrument is a test question. Hypothesis test conducted byparametric test is testing paired samples t test at a significant level of 0.05 withthe help of SPSS 23 for windows. The results of this study obtained t count of36,286 and a significant value of 0.00. Based on data analysis and hypothesistesting carried out obtained that: (1) There is an increase in student chemistrylearning outcomes through cooperative learning models think pair share atSMAN 92 Jakarta. (2) Increasing students' chemistry learning outcomes by usingthe cooperative learning model think pair share of 0.7 in the N-gain category,when compared to the conventional model of 0.67. Keywords: improvement, learning model, learning outcomes, and Think pairshare ABSTRAKPenelitian ini merupakan penelitian eksperimen murni dengan desain pre-testand post-test only control. Populasi meliputi seluruh siswa kelas XI MIPA SMAN92 Jakarta Semester I Tahun Pelajaran 2018/2019. Sampel penelitian terdiri daridua kelas dengan jumlah sampel 58 siswa yang ditentukan dengan purposivesampling. Instrumen penelitian berupa tes soal. Uji Hipotesis yang dilakukandengan uji parametrik yaitu uji paired samples t test pada taraf signifikan 0,05dengan bantuan SPSS 23 for windows. Hasil penelitian ini memperoleh t hitungsebesar 36,286 dan nilai signifikan 0,00. Berdasarkan analisis data dan ujihipotesis yang dilakukan diperoleh bahwa: (1) Terdapat peningkatan hasil belajarkimia siswa melalui model pembelajaran kooperatif tipe think pair share di SMAN92 Jakarta. (2) Peningkatan hasil belajar kimia siswa dengan meggunakan modelpembelajaran kooperatif tipe think pair share sebesar 0,7 dalam kategori N-gain,bila dibandingkan dengan model konvensional sebesar 0,67. Kata Kunci: peningkatan, model pembelajaran, hasil belajar dan think pair share